Object’s Border and Position Allocating in an X-Ray Image; Applied Mechanics and Materials; Vol. 756 : Mechanical Engineering, Automation and Control Systems (MEACS2014) - Tsapko I. V. Irina Valerievna (Image and Signal Processing, Recognition, Information Processing and Applied Technologies, 2015)
Title screen